THE PUZZLE OF INALIENABLE RIGHTS - Pino, Giorgio (Singapore journal of legal studies, 2024)
The idea of "inalienability" is normally thought of as providing the strongest level of protection that a right (and hence its right-holder) can possibly enjoy. Whereas an "ordinary" fundamental right is supposed to be protected first of all against the State ("vertical" protection), and secondly also against other private citizens and entities in general ("horizontal" protection), some rights are supposed to be so important that they are protected, it seems, even against the choices and decisions of the very right-holder. While the idea of an inalienable right is well known in legal, moral, and political philosophy, it is not entirely clear what it means for a right to be inalienable - and whether an inalienable right is really a right after all. By using a Hohfeldian conceptual framework, this essay tries to provide an analytical inquiry into the concept of an inalienable right, and to explore under what conditions it is conceptually possible to talk of inalienable rights.